RISKS OF MOTHER-TO-CHILD TRANSMISSION OF HIV: AN INTEGRATIVE REVIEW - Eduarda Almeida de Souza, Cicera; da Costa Araújo, Paulo; da Silva, Cleomar; Barbosa Gomes dos Santos, Fernanda; Olyntho Barreto Alves, Letícia; Orlando Farias Martins Filho, Antonio; Ferreira de Miranda, Izabel; da Costa Araújo, Bruna; Poliana de Sousa, Marília; Gomes Barreto, Renata (Health and Society, 2022)
Vertical transmission is a condition in which the virus is infected from mother to child and can have some consequences and risks during pregnancy and at the time of delivery. It is estimated that the incidence of vertical transmission occurs in 25% of pregnancies of infected women when there are no prophylactic measures and therapeutic interventions, resulting in high rates of mortality and disease progression. Contact with contaminated fluids can lead children to contract the virus in the first few months of life. The factors involved include several failures in the health system and maternity. Thus, the present study is based on the following justification: In health services and in the social context, there are difficulties and gaps that contribute to the risk factors of vertical transmission of HIV, constituting negative results for the control of the disease. In view of this, the objective of this research is to identify in the literature which are the existing difficulties that influence the prophylactic measures of vertical transmission. This study was carried out through an integrative literature review, through a survey of data in the scientific bases: LILACS, SCIELO and BDENF. The results obtained indicate that the failure to take prophylactic measures during pregnancy, due to negligence in prenatal consultations, is considered one of the aggravating factors for the risk of VT. Without early diagnosis, without knowledge of the virus, the pregnant woman does not undergo treatment with antiretroviral medication, with this, the immune system is more vulnerable to weakening and risks of complications during pregnancy.